Develop Bactra system to determine Mutagens in the Environment, Food Second: use Hashr agents acridine orange (Baghdad Science Journal, 2005)
Use Almtafr Alcderan orange, one of the factors Hashr Alttafaria to study Alatjabh isolates elected on the basis of specifications so that was a positive response with mutagen record and system consisting of three isolates used Alcderan orange graded concentrations and under specific Trov similar conditions Alttafar Pal NTG compared